Unsur Budaya Dalam Cerita Film Cakra Buana Karya Sutradara Massimo Burhanuddin - Dwiyanti, Revi; Suherman, Agus (UPI, 2019)
This research is motivated by the lack of research on film that uses Sundanese language and cultural settings. This study aims to describe the cultural elements that exist in the Cakra Buana film story. The method used in this research is descriptive analysis with document study techniques in the form of artwork. The data source in this study is the story of the film Cakra Buana by director Massimo Burhanuddin. The results of the study include 7 cultural elements, including: language, this film uses Sundanese language and undak usuk basa, knowledge systems are divided based on knowledge about nature and social, social organizations include government systems, how to replace leaders and designations of kinship, technological systems including tools, food, clothing, houses and means of transportation, the livelihood system that is farming, the religious system is still influenced by Hinduism and Buddhism because it uses the word